Tanggung Jawab Hukum Rumah Sakit Penyelenggara Telepsikiatri (Telemedicine) (RechtJiva, 2024)
Clinical procedures have been administered online by psychiatrists without complying with the psychiatric code of conduct. This situation has triggered illicit conduct that takes the victims who suffer from trauma and bruises, while such illegal practices have been found in some other victims who start to raise grievances on social media. Departing from this issue, this research is intended to delve into the negligence and the liability of the hospitals concerned in providing telemedicine services, particularly telepsychiatry within the scope of medical liability. This research aims to analyze the regulation of the liability held by the hospitals giving online mental health care consultation, or commonly dubbed telemedicine with a normative-juridical method and statutory and conceptual approaches. Primary, secondary, and tertiary data were analyzed using grammatical and systematic interpretations. The research results reveal that 1) the practice done by the psychiatrists as delineated above raises liability due to the negligence involved in the medical practice; 2) the hospitals concerned are held liable following the conduct and the nexus between the hospitals and doctors according to Article 193 of Law Number 17 of 2023 concerning the negligence and the provisions of sanctions. Indonesia can adapt sanction provisions from the Health Care Service Act (HCSA) issued by the Ministry of Health Singapore.